Unmet Needs Following Hospitilization with Heart Failure - Davidson, Patricia; Cockburn, J.; Newton, Phillip (Lippincott Williams and Wilkins, 2008)
Measuring health status is increasingly important in both clinical practice and research. The Heart Failure Needs Assessment Questionnaire (HFNAQ) is a self-administered, disease-specific, 30-item questionnaire that measures an individual's perception of his/her needs in the physical, psychological, social, and spiritual domains. To assess the prevalence of needs in patients with heart failure (HF) recently discharged from hospital.The HFNAQ was administered to participants (n = 132; mean (SD) age, 72.3 (9.96) years; 63% male) consenting to attend an HF-specific cardiac rehabilitation program.The total mean HFNAQ score was 67.3 (95% confidence interval, 65.03-69.75), indicating an average level of need around the midrange of the scale. In this vulnerable postdischarge phase, there was evidence of predominance of psychological and social concerns over physical needs. None of the variables that were examined for associations with the measures of needs reached statistical significance, highlighting the strongly individualized perception of need.Higher levels of unmet needs in the psychological and social domains, compared with physical needs, identify psychosocial care as an important consideration for nursing interventions for people with HF. This study further demonstrates the importance of assessing the needs from the perspective of the individual to ascertain each person's unique perspective of the HF illness experience. Study findings further underscore the importance of individualized care planning for patients with HF after discharge from hospital to address their unique needs and circumstances.